B-learning protocol for the higher alphabetization - Laplagne Sarmiento, Cristina (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This paper arose in order to disseminate the results achieved as participants of a transdisciplinary research team in the project on protocols needed in virtual education. We thus concluded that training in competencies, digital literacy and autonomy in learning should be prioritized in the teaching of undergraduate engineering courses. Previous studies confirmed the need to promote curricular changes through e-learning in B-learning format. With the same format, the gravitation of a curricular innovation protocol focused on literacy and digital literacy competencies, autonomy and critical thinking, following the indications for engineering education published by CONFEDI (2018), was investigated.